The Identity Issue of the Colonized and the Colonizer in Cloud Nine by Caryl Churchill - Putri, Liza; Clayton, Katherine (International Journal of Culture and Art Studies, 2020)
One of the significant points in post-colonial literature is identity issues. The analysis of these identity issues should be focused not only on the colonized character but also the colonialist. It is obvious why post-colonial scholars are concerned with the colonized as they are the victims of colonialism. However, the colonizer must also face complex issues of identity when arriving in the colonial place. The purpose of this article is to examine the identity issues undergone by Joshua, the colonial subject, and by Clive, the colonizer, with reference to Cloud Nine by Caryl Churchill in the colonial period. The concept of hybridity by Homi Bhabha can explain the issue of Joshuaâ€™s identity since he has â€œdoubleâ€ portrays of the identity as legacy of colonialism. Bhabha created the terms the â€œthird spaceâ€ or the â€œin-betweenâ€ to describe the condition of the colonized people. Clive as the colonizer used to be a person without particular authority in his own country before arriving to the colonial land. Suddenly, his identity has shifted into someone who has privileges and authority. The colonizerâ€™s identity is not complete without the colonized. The colonized and the colonizer depend on each other. The colonized and the colonizerâ€™s identities will be fragmented if one of them is missing.